Sports Medicine Australia and COVID-19: providing `virtual` support to the sports community - Mosler, A. B.; West, L. R. (British Journal of Sports Medicine, 2020)
The COVID-19 pandemic has sent shockwaves through the global sporting world with events and competitions postponed or cancelled. The impact on elite athletes, sporting organisations, people working in sport, and community-level sport has been extraordinary. While Sports Medicine Australia (SMA) has similarly faced considerable challenges, opportunities for the organisation to adapt and redirect its focus have presented as a result of the pandemic.